Synthesis of optimal and near-optimal biochar-based carbon management networks with P-graph - Aviso, Kathleen B. (Animo Repository, 2019)
The application of biochar to soil is a potentially significant way to achieve negative net emissions. Photosynthesis fixes carbon from the atmosphere during plant growth; subsequently, pyrolysis stabilizes the carbon in biomass into recalcitrant form, which results in long-term storage when the carbonized product is put in soil. However, effective planning of such Biochar-based Carbon Management Networks is needed to ensure that benefits are maximized, and that adverse consequences are mitigated. The objective of this work is to develop a P-graph methodology for planning Biochar-based Carbon Management Networks, where pyrolysis plants act as sources, while the agricultural lands that receive the biochar act as sinks. Two problem variants are considered. In the first case study, the allocation of biochar is constrained by the presence of contaminants that exist naturally in the biomass or are formed during pyrolysis, such that only 72.5% of the available biochar is applied to soil. In the second case study, the distribution of biochar is limited both by the ultimate soil carbon limit, as well as annual application rates at each site; 88.9% of the available biochar is used in the optimal solution. The P-graph framework also generates near-optimal network topologies, which present alternative solutions that can be useful for the large-scale implementation of Biochar-based Carbon Management Networks. © 2019 Elsevier Ltd